Biological Hydrogen Production Through Dark Fermentation with High-Solids Content: An Alternative to Enhance Organic Residues Degradation in Co-Digestion with Sewage Sludge - Rodolfo Daniel Silva-Martínez; Oscar Aguilar-Juárez; Lourdes Díaz-Jiménez; Blanca Estela Valdez-Guzmán; Brenda Aranda-Jaramillo; Salvador Carlos-Hernández (Fermentation)
Adequate treatment of the organic fraction of municipal solid waste (OFMSW) in co-digestion with sewage sludge (SS) through dark fermentation (DF) technologies has been widely studied and recognized. However, there is little experience with a high-solids approach, where practical and scalable conditions are established to lay the groundwork for further development of feasible industrial-scale projects. In this study, the biochemical hydrogen potential of OFMSW using a 7 L batch reactor at mesophilic conditions was evaluated. Parameters such as pH, redox potential, temperature, alkalinity, total solids, and substrate/inoculum ratio were adjusted and monitored. Biogas composition was analyzed by gas chromatography. The microbial characterization of SS and post-reaction percolate liquids was determined through metagenomics analyses. Results show a biohydrogen yield of 38.4 NmLH2/gVS OFMSW, which forms ~60% of the produced biogas. Aeration was proven to be an efficient inoculum pretreatment method, mainly to decrease the levels of methanogenic archaea and metabolic competition, and at the same time maintain the required total solid (TS) contents for high-solids conditions. The microbial community analysis reveals that biohydrogen production was carried out by specific anaerobic and aerobic bacteria, predominantly dominated by the phylum Firmicutes, including the genus Bacillus (44.63% of the total microbial community), Clostridium, Romboutsia, and the phylum Proteobacteria, with the genus Proteus.